Building cooperative capacity: the specialty coffee sector in Nicaragua. Issue 2 (11th November 2014) - Poole, Nigel; Donovan, Jason
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Within the context of widespread donor support for producer organizations, the purpose of this paper is to examine the impact of interventions aimed at rescuing a failed cooperative and improving performance and business linkages between grower-suppliers and international markets through enterprise development. Design/methodology/approach – The paper reports a case study of a Nicaraguan coffee cooperative, Soppexcca, which received substantial donor support at the time of the international coffee crisis between 1999 and 2004. The study used a framework of organizational structure, strategy, empowerment, and performance to assess business performance and sustainability. Quantitative and qualitative data collection focussed on asset building and changes during the period 2005-2009. Findings – Soppexcca achieved major advances in asset building. External interventions played a pivotal role in building organizational capacity to respond to buyers' demands and market-related shocks. Support was received not only from donors but also from supply chain partners and third-sector organizations. However, important gaps remain, and addressing these gaps requires changes in Soppexcca and sustained support. Research limitations/implications – As a case study, findings cannot be readily generalized but the implications will be of significance beyond the coffee sector in Nicaragua, wherever and in whatever sector building cooperative capacity is an important development objective. Social implications – Experience with Soppexcca shows that the creation of sustainable collective organizations is a long-term process, particularly in respect of building human capital. Originality/value – The paper examines enterprise development using concepts of capital asset formation and cooperative performance, and argues the significance of effective links between value chain stakeholders as well as internal cooperative performance.